Interaksi Simbolik Pekerja Seks Komersial High Class di Kalangan Mahasiswa Kota Padang - ELVA RONANING ROEM (Komunikator, 2014)
This paper is the result of research in Padang, West Sumatra, about sex business which is done by female college students who continue their study in this city. TThrough the research, it could be revealed that they become prostitutes not only because of economic factors but also because of their own need. Interpersonal communication in the form of persuasive communication and showing their trademark symbols both verbal and non-verbal are performed in order to attract their male customers. However, these high class prostitutes communicate differently when they play their role as female college students. Their symbolic interactions when become students are very much different from their night life. At campus, they only wear casual clothes, show casual appearance, and tend to choose certain people to be their friends. In addition, these kinds of students are still motivated to continue and finish their study. They do it not only for their own prestige but also for fulfilling their family demand to be educated intellectuals in the future. Keywords: High Class Prostitutes, Interpersonal Communication, Symbolic Interaction